Strategi Orang Tua Tunggal dalam Mendidik Akhlak Anak - Yazidul Busthomi; Lina Amanatul Khasanah (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2022)
The strategy of single parents in educating children's morals is as follows: 1). Giving advice, advice basically conveys a message from its source to those who need it, much of it in the Qur'an is in the form of advice that aims to raise awareness for those who listen or read it, in order to increase faith and piety to Allah. This advice is a very sacred form of coaching in shaping one's personality, especially in fostering children's prayer practices. 2). Exemplary, a very important thing for parents to pay attention to, especially single parents in order to foster children's morals, is exemplary. Moral issues must be given and accustomed to children, while parents are obliged to guide and educate their children to have noble character, this is an important part that must be carried out by parents. The most important part in educating children is to set a good example for them. 3). Habituation, educating morals are also instilled in children by providing guidance to them with habituation, meaning that our children are not only given understanding or theories and examples, they should be guided to be able to get used to good behavior, for example respecting parents and so on